The light at the end of the world - Deb, Siddhartha, 1970- (Soho Press, Inc., 2023)
"Delhi, the near future: a former journalist goes in search of answers after she finds herself stripped of identity and citizenship and thrust into a vast conspiracy involving secret detention centers, government sanctioned murders, online rage, nationalist violence, and a figure of shifting identifies known as the "New Delhi Monkey Man." Bhopal, 1984: an assassin hunts a whistleblower through a central Indian city that will shortly be the site of the worst industrial disaster in history. Calcutta, 1947: a veterinary student's life and work connect him to an ancient Vedic aircraft. And in 1859, a detachment of British soldiers rides toward the Himalayas in search of the last surviving leader of an anti-colonial rebellion. These timelines interweave to form a kaleidoscopic, epic novel in which each section is a pursuit, centered around a character who must find or recover crucial but hidden truths in their respective time. Mirroring the future and the past, these narratives illuminate and reimagine Indian identity and history. The Light at the End of the World, Siddhartha Deb's first novel in a decade and a half, is an astonishing work that brilliantly reimagines the structure of one of the world's oldest civilizations."--